Microstructural evaluation and corrosion behaviour of Fe-Cr-Ni-Mn-Co AND AI0.5-Fe-Cr-Ni-Mn-Co highentropy alloys (HEA) with elemental additions / Siti Sarah Mohd Pauzi - Mohd Pauzi, Siti Sarah (Institute of Graduate Studies, UiTM, 2018)
Equiatomic or near-equiatomic multicomponent alloys, often termed as high-entropy alloys (HEAs), are an emerging class of metallic materials that are being investigated for a wide range of technical applications. Most studies have been focused on optimizing microstructures or mechanical properties of HEAs and relatively few have designed an alloy for investigating corrosion behavior of HEAs. This study describes the microstructural and corrosion behaviour together with mechanical properties of six HEAs that were designed with the intent to provide high corrosion resistance whilst offering the possibility for high temperature applications. The basic components of the alloys are composed of five elements that are commonly utilized in high temperature alloys, Fe, Cr, Ni, Mn and Co. A sixth element, Al, was also added. Another elements that had been selected as the alloying elements, particularly due to their remarkable properties were Zr, Ta and Sc. Detailed microstructural and chemical analysis have confirmed the presence of the expected BCC and FCC solid solution phases, however, the minority phases in all of the alloys were found to be ordered intermetallics. The hardness investigation demonstrated that the hardness values increased gradually for all alloys due to the formation of the intermetallic compounds…